ANALISIS MISKONSEPSI SISWA MATERI UNGGAH-UNGGUH BAHASA JAWA MENGGUNAKAN INSTRUMEN THREE-TIER TEST PADA SISWA KELAS V SD - Amantiya Putri, Cindy; Itsna Sholihah, Nur; Khusna Inayah, Uty; Ayu Retnoningsih, Diyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to identify students' misconceptions regarding Javanese speech levels (unggah-ungguh) among fifth-grade students at SD Negeri Jatisawit 03 using a Three-Tier Multiple Choice Test. A descriptive quantitative approach was employed with a saturated sample of 26 students. The research instrument consisted of 20 test items developed based on eight learning indicators. Data were analyzed descriptively using percentages. The results showed that 38.0% of the students demonstrated correct concept understanding, whereas 39.2% experienced misconceptions. The remaining students were categorized as guessing (8.3%), partial understanding (4.4%), and lack of understanding (9.5%). The highest misconception rate was found in item 19 (46%), followed by items 5 (34%), 9 (30%), 2 (26%), and 14 and 20 (23%). These findings indicate that students still have difficulty applying appropriate Javanese speech levels in different communication contexts. Therefore, contextual, interactive, and practice-based learning strategies are needed to reduce students' misconceptions.